Influence of bee family care on honey productivity in hives of different constructions - Kakhramanov Boymakhmat; Akmalkhanov Talat; Soatov Utkir (E3S Web of Conferences, 2023)
It is of great importance to design and manufacture light and cheap hives that are easy to operate and easy to operate in normal beekeeping conditions. Several types of hives are used depending on the breed, origin, lifestyle and climate of the bees. In the warm climate of Uzbekistan, the most commonly used hive in beekeeping is the bee hive. There are mainly three types of hives used in beekeeping, i.e. bed hives, double hives and multi-storey hives. Studying which types of nests to use in the hot climate of Uzbekistan and their effect on family productivity is one of the urgent issues of today. The natural climatic conditions of Uzbekistan have a favorable opportunity to increase the productivity of agricultural crops, feed bee colonies based on modern advanced technologies, and increase the production of bee products. In this article, keeping bee families in hives of different constructions in the conditions of the Tashkent region, studying the effect on the productivity of families, determining the suitable bee hive suitable for hot climate conditions is studied.